Brien McMahon papers - McMahon, Brien, 1903-1952.
Correspondence, memoranda, speeches, addresses, articles, bills and resolutions, press releases, clippings, and printed material relating to McMahon's service in the U.S. Senate, including his years as chairman of the Joint Committee on Atomic Energy. Subjects include nuclear policy, the peaceful uses of atomic energy, and foreign affairs in the post-World War II period, especially in relation to Eastern Europe and the Soviet Union.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
U.S. senator from Connecticut.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Congress. -- Joint Committee on Atomic Energy; Nuclear energy -- Government policy -- United States; Europe, Eastern -- Foreign relations -- United States; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- Europe, Eastern; United States -- Foreign relations -- Soviet Union; United States -- Politics and government -- 1933-1953.; Senators, U.S. Congress -- Connecticut